Challenges and Benefits of Blended Learning in University EFL Reading Comprehension: A Mixed-Method Study - Dagnachew Tsegaye; Girma Gezahegn (Journal of English Language Teaching and Literature)
This study investigates the challenges and benefits experienced by students in the implementation of blended learning (BL) in English as a Foreign Language (EFL) reading classes. The research focuses on exploring the experiences of first year university students engaged in BL-based reading comprehension. Using a mixed-method approach, data was collected from 36 participants enrolled in a noncredit reading skills course integrated with a BL platform over 16-weeks. Participants completed a 16-item questionnaire, and a subset of ten students engaged in a focus group discussion to delve deeper into the challenges and benefits of BL. Descriptive statistics (e.g., frequency, percentages) were employed for quantitative data analysis, while qualitative data were analyzed through thematic identification. The findings revealed significant challenges including technology issues, language barriers, and initial confusion with BL tools. Participants emphasized the critical need for reliable technology infrastructure, support for digital literacy, and language assistance to mitigate these obstacles. Despite these challenges, participants acknowledged BL's advantages, particularly its flexibility and accessibility in enhancing reading comprehension. Recommendations arising from the study advocate for personalized learning paths, collaborative activities, clear communication, and ongoing assessment to optimize BL implementation. Thus, this research underscores BL's potential in improving reading skills, highlighting the imperative of tailored support to effectively address implementation challenges. The study could also become more thorough and broadly applicable to other Ethiopian universities by increasing the sample size and extending the intervention period.